2008
DOI: 10.1111/j.1467-8527.2008.00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Identity and School History: The Perspective of Young People From the Netherlands and England

Abstract: The article presents the findings from a survey of over 400 young people in metropolitan areas in the Netherlands and England concerning their views on identity and school history. The research explored pupils' ideas about which facets of history were of interest to them, what history they believed should be taught in schools, and their views on the purposes of school history and history in general. The coding of the data made it possible to delineate between those from different ethnic minority backgrounds, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 11 publications
2
38
0
1
Order By: Relevance
“…Although informants indicated that immigrants seeking citizenship should 'pass a test which proves they understand our national history and cultures' (mean score ¼ 3.19), the mean scores for items tapping an authoritarian view of history are all below the median possible score. This mirrors evidence from a recent study, which suggested that young people may be resistant to traditional approaches to history (Grever, Haydn, and Ribbens 2008). Broad underlying attitudes amongst students were revealed through exploratory factor analysis of the seven survey items, which produced two statistically significant …”
Section: Research Methods Context and Datasupporting
confidence: 55%
See 1 more Smart Citation
“…Although informants indicated that immigrants seeking citizenship should 'pass a test which proves they understand our national history and cultures' (mean score ¼ 3.19), the mean scores for items tapping an authoritarian view of history are all below the median possible score. This mirrors evidence from a recent study, which suggested that young people may be resistant to traditional approaches to history (Grever, Haydn, and Ribbens 2008). Broad underlying attitudes amongst students were revealed through exploratory factor analysis of the seven survey items, which produced two statistically significant …”
Section: Research Methods Context and Datasupporting
confidence: 55%
“…In particular, despite the existence of a small literature analysing students' attitudes towards history teaching and identity (e.g. Carrington and Short 1998;Barton and McCully 2005), to date, few empirical studies have systematically examined their association with sources of self-identity, especially amongst those who have recently completed their period of secondary education (Cinnirella 1997;Grever, Haydn and Ribbens 2008).…”
Section: Introductionmentioning
confidence: 98%
“…The static, fixed and exclusionary interpretation of national identity and the (political) uses of history in national identity construction have been evaluated negatively several times over (Grever, Haydn, & Ribbens, 2008;Grever, Pelzer, & Haydn, 2011;Ribbens, 2007). History may be readily used as a means to make claims in the struggles over national history and identity.…”
Section: Modernization and History Education In The Maghrebmentioning
confidence: 99%
“…Another danger in reverting to the traditional model of school history that operated in most English schools until the 1970s is that the assumption that teaching a positive story of the national past will promote social cohesion is an illusory and untested one. Research by Grever et al [48] found that a majority of young people in England and the Netherlands did not agree with the suggestion that 'a common history promotes common bonds'. Martin Walker also points out that attempts to use history teaching as an instrument of socialization have proved to be ineffective in the past:…”
Section: A Note Of Caution About the Possible Dangers And Disadvantagmentioning
confidence: 91%